Analisis Makna Al-Maut dalam Perspektif Al-Qur’an - Masyhuri Rifa’i; Irdawati Saputri; Ros Mayasari; Subria Mamis; Samsuri (Gunung Djati Conference Series, 2022)
This study aims to discuss the meaning of the word al-maut in the perspective of the Qur'an. This study uses a descriptive-analytical qualitative approach. The object of study in this study is the verses of the Qur'an. Therefore, the author uses the Maudhu'i interpretation method with exegetical, theological, and sociological analysis. The results of this study indicate that the word al-maut is linguistically the departure or loss of power and strength of something. The views of the Qur'an about death include a transition to the grave, when and where and all by Allah's permission. While the function of al-maut in general is as a test for living beings.